2017
DOI: 10.1039/c7ra04875k
|View full text |Cite
|
Sign up to set email alerts
|

Water-based synthesis of zeolitic imidazolate framework-8 for CO2 capture

Abstract: a This paper studies the impacts of five key synthesis parameters of zeolitic imidazolate framework-8 (ZIF-8) in an aqueous solution, namely zinc resource, pH value, temperature, reaction time, and the concentration of water in the ligand (H 2 O/Hmim). It was found that the crystallization of ZIF-8 samples is strongly impacted by these synthesis parameters. ZIF-8 synthesized at a temperature of 85 C, reaction time of 5 min, and pH value of 11.4 had a large special surface area and pore volume, and thus had a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 43 publications
3
24
0
Order By: Relevance
“…The reaction times of 30 and 60 min were still in the crystal growth phase, such that the formation of ZIF-L had not been completed. Previous studies reported that the ZIF’s characteristics in terms of surface area and pore volume increased during the crystal growth phase until a certain time, and then remained constant [ 2 , 20 ]. However, Figure 2 shows the decreased value of ZIF-L synthesized for a reaction time of 180 min.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reaction times of 30 and 60 min were still in the crystal growth phase, such that the formation of ZIF-L had not been completed. Previous studies reported that the ZIF’s characteristics in terms of surface area and pore volume increased during the crystal growth phase until a certain time, and then remained constant [ 2 , 20 ]. However, Figure 2 shows the decreased value of ZIF-L synthesized for a reaction time of 180 min.…”
Section: Resultsmentioning
confidence: 99%
“…The highest value was obtained at a temperature of 30 °C. A previous study reported that ZIFs with a high crystallinity and surface area could be obtained at a specific temperature [ 20 ]. The crystallinity and surface area were the main characteristics that affected the value.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, considerable efforts have been devoted to synthesize ZIF‐8 in green and facile, for example in an aqueous medium at room temperature . Shi et al reported that synthesis of ZIF‐8 in an aqueous medium is highly influenced by zinc source, pH, temperature, reaction time, and concentration of water in the ligand . Pan et al reported synthesizing ZIF‐8 in 5 min, in an aqueous medium, with a microporous volume of about 0.31 cm 3 g −1 .…”
Section: Introductionmentioning
confidence: 99%